2021
DOI: 10.1016/j.molmet.2020.101102
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists in the treatment of type 2 diabetes – state-of-the-art

Abstract: Background GLP-1 receptor agonists (GLP-1 RAs) with exenatide b.i.d. first approved to treat type 2 diabetes in 2005 have been further developed to yield effective compounds/preparations that have overcome the original problem of rapid elimination (short half-life), initially necessitating short intervals between injections (twice daily for exenatide b.i.d.). Scope of review To summarize current knowledge about GLP-1 receptor agonist. Major conclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
680
0
39

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 832 publications
(735 citation statements)
references
References 239 publications
(193 reference statements)
16
680
0
39
Order By: Relevance
“…These results not only suggest a strong link between psoriasis and diabetes, but also suggest that the two diseases may share an inflammatory pathophysiology [34]. In terms of its association with diabetes, there is increasing evidence of the positive effects of anti-diabetic drugs on psoriasis including glucagon-like peptide-1 (GLP-1) receptor agonists, dipeptidyl peptidase-4 (DPP-4) inhibitors, thiazolidinedione and biguanide [35][36][37][38][39][40]. Therefore, it is important to summarize the clinical data that shows the anti-psoriatic effect of anti-hyperglycemic drugs and discuss their potential mechanisms of action.…”
Section: Psoriasismentioning
confidence: 96%
“…These results not only suggest a strong link between psoriasis and diabetes, but also suggest that the two diseases may share an inflammatory pathophysiology [34]. In terms of its association with diabetes, there is increasing evidence of the positive effects of anti-diabetic drugs on psoriasis including glucagon-like peptide-1 (GLP-1) receptor agonists, dipeptidyl peptidase-4 (DPP-4) inhibitors, thiazolidinedione and biguanide [35][36][37][38][39][40]. Therefore, it is important to summarize the clinical data that shows the anti-psoriatic effect of anti-hyperglycemic drugs and discuss their potential mechanisms of action.…”
Section: Psoriasismentioning
confidence: 96%
“…Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are a class of subcutaneous glucose-lowering drugs approved for the treatment of T2DM [22]. Large RCTs on GLP-1 RAs have also consistently demonstrated that these drugs exert beneficial effects on the risk of adverse cardiovascular outcomes, all-cause mortality and worsening of nephropathy in patients with T2DM [22][23][24]. GLP-1 RAs improve glycemic control while also reducing body weight and insulin resistance [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has a half-life of up to 2.4 h, 10 times longer than endogenous GLP1, because its resistance to human DPP4 degradation [ 81 , 82 ]. Since the first generated GLP1As have a subcutaneous administration twice daily, other compounds have been developed to extend durability [ 84 ]. The optimization approach was addressed to keep the human GLP1 backbone to avoid immunogenic problems [ 84 ] and to get DPP4 action resistance through GLP1-(7-36) region modifications [ 26 , 81 ].…”
Section: Therapies Based On the Incretin Systemmentioning
confidence: 99%
“…Since the first generated GLP1As have a subcutaneous administration twice daily, other compounds have been developed to extend durability [ 84 ]. The optimization approach was addressed to keep the human GLP1 backbone to avoid immunogenic problems [ 84 ] and to get DPP4 action resistance through GLP1-(7-36) region modifications [ 26 , 81 ]. These modifications consist in the replacement of the penultimate alanine at the N-terminal end of the peptide by a glycine, serine, D-alanine, or by the most optimal chemical group, aminoisobutyric acid (Aib) [ 80 ], since it does not interfere with GLP1 receptor binding [ 85 ].…”
Section: Therapies Based On the Incretin Systemmentioning
confidence: 99%
See 1 more Smart Citation